Strategic behavior and international benchmarking for monopoly price regulation: The case of Mexico - Dagobert L. Brito; Juan Rosellón (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper looks into various models that address strategic behavior in the supply of gas by the Mexican monopoly Pemex. The paper has three very strong technical results. First, the netback pricing rule for the price of domestic natural gas (based on a Houston benchmark price) leads to discontinuities in Pemex's revenue function. Second, having Pemex pay for the gas it uses and the gas it flares increases the value of the Lagrange multiplier associated with the gas processing constraint. Third, if the gas processing constraint is binding, having Pemex pay for the gas it uses and flares does not change the short run optimal solution for the optimization problem, so it will have no impact on short-run behavior. These results imply three clear policy recommendations. The first is that the arbitrage point be fixed by the amount of gas Pemex has the potential to supply in the absence of processing and gathering constraints. The second is that Pemex be charged for the gas it uses in production and the gas it flares. The third is that investment in gas processing and pipeline should be in a separate account from other Pemex investment.
Keywords: L51; L95; Q4; Q48; 330; Natural gas; strategic pricing; benchmark regulation; gas pipelines; Mexico; Gaspreis; Monopol; Staatliche Preispolitik; Gasleitungstransport; Netzzugang; Mexiko